Associating Social Determinants of Health With PROMIS CAT Scores and Health Care Utilization After ACL Reconstruction. Issue 1 (13th January 2023) - Ziedas, Alexander; Castle, Joshua P.; Abed, Varag; Swantek, Alexander; Chaides, Sarah; Elhage, Kareem; Fife, Johnathan; Moutzouros, Vasilios; Makhni, Eric C.
Background: The term "social determinants of health" (SDOH) refers to social and economic factors that influence a patient's health status. The effect of SDOH on the Patient-Reported Outcomes Measurement Information System (PROMIS) computer adaptive test (CAT) scores and postoperative resource utilization in patients with anterior cruciate ligament reconstruction (ACLR) have yet to be thoroughly studied. Purpose: To investigate the impact SDOH have on PROMIS CAT outcomes and postoperative resource utilization in patients with ACLR. Study Design: Cohort study; Level of evidence, 3. Methods: The electronic medical record was used to identify the SDOH for patients who underwent ACLR by 1 of 3 sports medicine fellowship–trained orthopaedic surgeons between July 2017 and April 2020. PROMIS CAT measures of Physical Function (PROMIS-PF), Pain Interference (PROMIS-PI), and Depression (PROMIS-D) were completed at the preoperative, 6-month postoperative, and 12-month postoperative time points. Postoperative health care utilization was recorded as well. Independent 2-group t tests and Wilcoxon rank-sum tests were used to analyze mean differences between patient groups based on SDOH. Results: Two-hundred and thirty patients who underwent ACLR were included (mean age, 27 years; 59% male). Compared with White patients, Black patients were represented more frequently in the lowest median household income (MHI) quartile (63% vs 23%, respectively; P < .001). White patients were represented more frequently in the highest area deprivation index (ADI) quartile when compared with Black patients (67% vs 12%, respectively; P = .006). Significantly worse PROMIS-PF, PROMIS-PI, and PROMIS-D scores at all 3 time points were found among patients who were Black, female, smokers, and in the lower MHI quartiles, with higher ADI and public health care coverage. In terms of resource utilization, Black patients attended significantly fewer postoperative physical therapy visits when compared with their respective counterparts. Those in the lower MHI quartiles attended significantly fewer postoperative imaging encounters, and female patients attended significantly more postoperative virtual encounters than male patients. Conclusion: Specific SDOH variables, particularly those that reflect racial and socioeconomic disparities, were associated with differences in postoperative health care utilization and ACLR outcomes as measured by PROMIS CAT domains.